The molecular pathway triggered by zirconia in endothelial cells involves epigenetic control - da C. Fernandes, Célio Júnior [UNESP]; da Silva, Rodrigo A.; Fretes Wood, Patrícia [UNESP]; Teixeira, Suélen Aparecida [UNESP]; Bezerra, Fábio [UNESP]; Zambuzzi, Willian F. [UNESP] (Elsevier, 2021)
The requirement to achieve natural looking restorations is one of the most challenging aspects in dentistry. Although zirconia has provided new opportunities for achieving superior aesthetics and physicochemical outcomes, very little has been achieved for its cellular and molecular performance, especially considering angiogenesis and osteogenesis. As angiogenesis is a secondary event and concomitant to osteogenesis, an indirect effect of dental implant on endothelial cells could be the release of active molecules such as those already reported affecting osteoblasts. To better address this issue, we challenged human endothelial cells (HUVECs) with zirconia-conditioned medium up to 72 h to allow analysis specific gene expression and protein pattern of mediators of epigenetic machinery in full. Our data shows involvement of zirconia in triggering intracellular signaling through MAPK-ERK activation, leading the signal to activate histone deacetylase HDAC6 likely with concomitant well-modulated DNA methylation profile by DNMTs and TETs. These signaling pathways seem to culminate in cytoskeleton rearrangement of endothelial cells, an important prerequisite to cell migration expected in angiogenesis. Collectively, this study demonstrates for the first time epigenetic-related molecular mechanism involved in endothelial cells responding to zirconia, revealing a repertoire of signaling molecules capable of executing the reprogramming process of gene expression, which are necessary to drive cell proliferation, migration, and consequently angiogenesis. This set of data can further studies using gene editing approaches to better elucidate functional roles.
Keywords: Angiogenesis; Biomaterial; Cell behavior; Dental materials; Endothelial; Zirconia